(untitled) (Malaysian Journal of Civil Engineering, 2023)
The contents of many books, prima facie, can be known by their title. But within the context of the present day grammatical construction and images formed in the mind through some words, Vitruvius’s “Ten Books on Architecture”, written in 1st century, does not fall into this category. Apparently, the over 2000 year’s gap in knowledge and usage of precepts as well as educational attainment that formed the basis for the writing constituted unfamiliar background and terrain for the 21st century researchers and academia. Consequently many civil engineering developmental resources for research activities contained in the book, especially on concrete and structural materials, remain hidden from many researchers. The purpose of this work is to identify the depths of instructional and educational attainment, both in learning and practice that formed the background for writing and thus, for the understanding of the book, especially for engineers in the developing Nations. To accomplish this work, the Roman society of the time and her educational systems were studied from materials available from the public domain. Analysis of the materials obtained showed that a wide-range and multi-faceted education through learning and practice, were required to operate in the construction industry at the time; and that all construction work, including military and machine construction were termed Architecture and under the control of the Head of the Government. It is also concluded that this learning, now parceled into different disciplines, is available in the public domain for the understanding and application of precepts in the Ten Books on Architecture for a robust structural and civil engineering practice